Violencia contra la mujer en el Cantar de Mío Cid y en el Nibelungenlied - Acosta, Luis A. (Revista de Filología Alemana, 2009)
Based upon an only literary inquiry we can appreciate in Mío Cid that aim of the main figures to attain their purposes, grounds after all on a trading system where prevails the pure exchange value. At the same time function of the poet is to give answer to the preservation of a social system where dominate advantages for men. In Nibelungenlied the social and ethic background is similar, nevertheless the literary development of the text is much more extensive and complicated, what doesn’t exclude that the structure, development and ending of the conflict become basically, as well as in Cantar de Mío Cid advantageous for men.
Keywords: Vilence against wife; Poetry of exchange value and of the law interpose